TINGKAT PARTISIPASI MASYARAKAT TERHADAP PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR JALAN DESA PELUKAHAN KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Tri Musliyatun; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted in the Pelukahan village Kuantan Hilir Seberang Kabupaten Kuantan Singingi. This study aims to determine how the public participation in the implementation of road infrastructure construction and to know what are the factors that influence public participation in the implementation of road infrastructure construction. This study, entitled